RETRACTED: Baicalin Induced Dendritic Cell Apoptosis in Vitro - Zhang, Huahua; Jiao, Qingqing; Gong, Qianfeng; Zhang, Yan; Zhang, Weidong; Hu, Zhenlin (Frontiers in Pharmacology, 2011)
This study was aimed to investigate the effects of Baicalin (BA), a major flavonoid constituent found in the herb Baikal skullcap, on dendritic cells (DCs). DCs were generated by culturing murine bone marrow cells for 6 days with granulocyte-macrophage colony-stimulating factor and interleukin-4, and lipopolysaccharide (LPS) was added on day 5 to stimulate DCs maturation. The expression levels of DC maturity markers (CD80/CD86) were assessed by flow cytometry using direct immunofluorescence method. Interleukin-12 (IL-12) levels in the culture supernatants were assayed by ELISA. Apoptosis of DCs was analyzed by flow cytometry after Annexin V/propidium iodide staining. The mitochondrial membrane potential changes were measured by using the J-aggregate forming lipophilic cation 5,5',6,6'-tetrachloro-1,1',3,3'-tetraethylbenzimidazolcarbocyanine iodide (JC-1). Exposure of DCs to BA (2-50 microM) during bone marrow cell differentiation showed no effects on the up-regulation of CD80/CD86 expression on DCs in response to LPS stimulation, but reduced DCs recovery by inducing apoptosis, and significantly inhibited the release of IL-12 to culture supernatants. BA induced DC apoptosis in a time- and dose-dependent way, and immature DCs were more sensitive for BA-induced apoptosis than mature DC. BA also induced mitochondrial membrane potential changes in DCs. These results demonstrate that BA induces selective apoptosis in immature DCs possibly through mitochondria-mediated pathway.